Investment Decisions: Mediating Role of Financial Behavior on Young Investors in the Capital Market - Terre Liyanty; Dela Jovam Sari; Benny Dhevyanto; Krisdiana Krisdiana (Rescollacom (Research Collaborations Community), 2025)
Interest in capital market investments continues to increase, along with improved access to information and digital platforms that make it easier for the younger generation to invest. However, psychological phenomena such as FOMO (Fear of Missing Out), YOLO (You Only Live Once) and FOPO (Fear of Other People`s Opinions) often affect their investment decisions. FOMO, in particular, can cause young investors to make rash investment decisions without careful consideration. This study aims to empirically test whether financial knowledge and risk preferences affect investment decision which mediated by financial behavior. Research used quantitative methods with descriptive, statistical analysis, and a sample of 150 respondents who were young investors aged 18-30 years in Cirebon. The findings of the analysis indicated that financial knowledge and risk preferences influences investment decision, and financial behavior successful as a mediator. It can be inferred that increasing financial knowledge and understanding of risk preferences can help young people make more rational investment decisions, despite the influence of psychological factors such as FOMO and others.